Analysis of Students' Numeracy Literacy Ability in Solving Three Variable Linear Equation System (SPLTV) Problems Based on Learning Styles - Fitriyani, Alfiyah; Pradipta, Trisna Roy (Universitas Pendidikan Mandalika, 2025)
This study aims to analyze students' numeracy literacy skills in solving Three Variable Linear Equation System (SPLTV) problems based on learning styles, namely visual, auditory, and kinesthetic. This study uses a qualitative approach with a case study design. The subjects were three students of class X at SMAN 88 Jakarta, selected using purposive sampling technique. Data were obtained through learning style questionnaires, numeracy literacy ability tests, interviews, and documentation, then analyzed using triangulation techniques to ensure data validity. The results showed that students with visual learning styles had quite good abilities in the aspect of mathematical modeling and making conclusions. Students with an auditory learning style show better ability to understand information, create mathematical models, interpret results and draw conclusions appropriately. Students with kinesthetic learning styles have quite good ability to interpret results and conclude results practically. Although each learning style has its own advantages, auditory learning styles tend to be better at achieving numeracy literacy skills than visual and kinesthetic learning styles. This study shows the importance for educators to understand the learning styles of students in order to be able to implement appropriate learning strategies and the researcher is further advised to consider other factors to gradually improve numeracy literacy skills.